Feasibility of prefronto-caudate pathway tractography using high resolution diffusion tensor tractography data at 3 T - Kamali, Arash (2010)
Mapping the human brain frontostriatal pathways using non-invasive diffusion tensor imaging (DTI) has been hampered by the inadequate imaging sensitivity, poor spatial resolution, lower tensor anisotropy within gray matter, increased partial volume averaging effects and poor signal-to-noise ratio. We investigated for the first time the utility of high spatial resolution DTI-based fiber-tractography using the fiber assignment by continuous tracking (FACT) to reconstruct and quantify bilaterally the prefronto-caudo-thalamic connections within the human brain at 3 T. Five healthy right-handed men (age range 24–37 years) were studied. We traced the anterior thalamic radiation and prefronto-caudo-thalamic pathways bilaterally and measured the volume of each tract and the corresponding diffusion tensor metrics in all subjects. The anterior thalamic radiation tract volume and corresponding fractional anisotropy (FA) were significantly larger bilaterally than prefronto-caudate pathway, whereas the mean diffusivity (D(av)) values were similar (p > 0.7). For both anterior thalamic radiation and prefronto-caudate pathway the tract volume and corresponding DTI metrics (FA, D(av)) were not significantly different between the two hemispheres (p > 0.2). Our DTI acquisition protocol and analysis permitted the reconstruction of the connectivity of the caudate with the thalamus as well as with the prefrontal cortex and allowed tracking of the whole trajectory of the prefronto-caudo-thalamic pathway.